Stratospheric Connection to the Abrupt End of the 2016/2017 Iberian Drought. Issue 22 (29th November 2018) - Ayarzagüena, B.; Barriopedro, D.; Garrido‐Perez, J. M.; Abalos, M.; de la Cámara, A.; García‐Herrera, R.; Calvo, N.; Ordóñez, C.
Abstract: Southwestern Europe experienced extraordinary rainy and windy conditions in March 2018, leading to the end of the most severe drought since 1970 at continental scale. This anomalous weather was linked to a persistent negative North Atlantic Oscillation pattern. Two weeks earlier a sudden stratospheric warming (SSW) took place, preceded by the strongest planetary wave activity on record. In this study, we explore the connection between the SSW and the weather shift by employing a weather regime approach and flow analogues. The timing of the downward propagation of the stratospheric anomalies, the transition to and persistence of the negative North Atlantic Oscillation weather regime, and the sudden precipitation increase are all consistent with the typical tropospheric state after SSWs. Our results evidence a significant role of the 2018 SSW in the record‐breaking precipitation event. Plain Language Summary: March 2018 was characterized by extraordinary heavy rain and strong winds over the Iberian Peninsula that ended the most severe drought since 1970 at continental scale. Two weeks earlier the polar stratosphere experienced anomalous conditions with a sudden rise in temperature, so‐called sudden stratospheric warming (SSW). Although SSWs are not rare events, the 2018 case was remarkable in terms of its intensity and persistence. The coincidence in time of both extreme events and the known link between SSWs and anomalous weather in the North Atlantic led the media to claim that the SSW was the main culprit of the anomalous weather of March 2018. However, this assumption is not straightforward because of the large variability in the magnitude of tropospheric responses to SSWs. Here we explore the role of the SSW in the abrupt weather shift by analyzing the downward propagation of the SSW signal and its link to the tropospheric synoptic conditions. Our results indicate an actual connection between the 2018 SSW and the record‐breaking precipitation event. Key Points: Outstanding stratospheric and tropospheric conditions occurred in late winter 2018, with a persistent SSW and extreme Iberian precipitation The rainy conditions were associated with an extremely persistent negative NAO pattern The 2018 SSW played a relevant role in the shift to and maintenance of the negative NAO event that ended the severe Iberian drought